Penerapan Arbitrase dalam Penyelesaian Perjanjian Leasing Kendaraan Bermotor - Yazid Aulia Rahman (Jurnal Hukum Lex Generalis, 2025)
Leasing is financing in the form of providing goods within a certain period of time and scheduled. Based on research at BPSK Surabaya, the leasing agreement was carried out verbally, between Moch Dachlan HN as the lessee and PT Summit Otto Finance as the lessor with the object of the agreement in the form of a Vario motorcycle with license plate L 4657 UF. After the credit is completed and repayment is made, the lessor cannot provide BPKB to the lessee's heirs on behalf of Nur Siyamah due to lack of evidence. This research uses a type of juridical - empirical research method. This type of research emphasizes the effectiveness of the law that is currently prevailing in society which is the basis for finding the facts and data needed to complete this research. Based on the problem, the heirs filed a lawsuit against PT Summit Otto at BPSK Surabaya. The parties chose arbitration as a dispute resolution method for several reasons such as effectiveness, flexibility, economic cost, and legal certainty. Although there were some obstacles such as the lack of attention of the lessor as the Respondent to the BPSK summons, the arbitration hearing showed that the lessor admitted that it was less cooperative in making the agreement and resolving the problems arising from the agreement. At the hearing, the lessor agreed to hand over the BPKB to the lessee's heirs with the fulfillment of several administrative requirements as proof of legal ownership.